Development of a Perforated Panel for Acoustic Conditioning Based on Colombian Guadua Fiber (Guadua Angustifolia Kunth) - Páez Soto, Darío Alfonso; Herrera Fernández, Luis Jorge; Acosta Agudelo, Oscar Esneider; García Bustos, Shymmy Wilbermer; Herrera Martínez, Marcelo (TECCIENCIA, 2018)
The present research is about the practical implementation of a perforated panel for acoustic conditioning, manufactured with guadua, a typical Colombian fiber. The developed panel is checked for its acoustic conditioning properties. Guadua is an attractive natural resource with great potential for renovation and use in sustainable construction. Here, its acoustic absorption coefficient is measured and validated; finally, a physical panel is built for acoustic conditioning purposes.